Student’s Perception Towards the Use of ICT in Improving English Speaking Skill in Boarding School - Hasanah, Alya Sofirotul; Alfisuma, Meria Zakiyah; Pujiati, Tri (Universitas Muhammadiyah Tangerang, 2025)
The main problem in this study is the use of teaching methods that are still conventional in Islamic boarding schools in learning English. This causes students to feel bored and less motivated to participate in English learning activities in Islamic boarding schools so innovation is needed in learning English by applying information and communication technology (ICT). This study aimed to investigate students’ perceptions of using information and communication technology (ICT), such as LCD Projectors and Microsoft PowerPoint, to improve English speaking skills at the boarding school. The study was conducted at a boarding school in Bangkalan, involving 42 students, consisting of 24 science students and 18 social science students. The method was descriptive qualitative, with data collected through a Google Form questionnaire. The results showed that the majority of students, 54.94%, had a positive view of using ICT, considering it effective in improving speaking skills and boosting confidence. In addition, the use of ICT was also found to increase student engagement and create a more interactive learning environment. The results of this study provide recommendations that the use of ICT in English learning in Islamic boarding schools is effective for use as a learning medium.